Production of Recombinant Envelope Proteins of Newcastle Disease Virus in Escherichia Coli and Analysis of Their Immunological Properties - Wong, Sing King (2005)
Newcastle disease virus (NDV) is the causative agent of the Newcastle disease (ND) thatremains as a major threat to the world poultry industry. The virus belongs to the family Paramyxoviridae and genus Avulavirus, infects more than 236 avian species, and causes up to 100% morbidity and mortality in susceptible birds. The viral envelope proteins, haemagglutinin-neuraminidase (HN) and fusion (F) proteins have been shown to play key roles in triggering the host immune responses. In order to study the immunological properties of the recombinant HN and F proteins, the HN and F genes of the Malaysian viscerotropic-velogenic NDV strain AF2240 were obtained through reverse transcription-polymerase chain reaction (RT-PCR) and cloned into the Pichia pastoris, Saccharomyces cerevisiae and Escherichia coli expression vectors. A number of eight recombinant plasmids were constructed, namely pPICZaA/HN and pPICZaA/F (P. pastoris system), pYES2a/HN and pYES2a/F (S. cerevisiae system),and pRSETA/HN, pRSETB/F, pET-43.1a/HN and pET-43.1a/F (E. coli system). The recombinant plasmids were used to transform respective host cells, which were then induced for the production of the recombinant HN and F proteins. However, there was no protein expression observed in the recombinant P. pastoris and S. cerevisiae cells. Whereas, the bacterial hosts were found expressing the recombinant HN and F proteins (from the pRSETA/HN and pRSETB/F plasmids respectively), and the NusA fusion proteins, NusA-HN and NusA-F (from the pET-43.1a/HN and pET-43.1a/F plasmids respectively). The recombinant HN and F proteins were produced as insoluble inclusion bodies (IB) while the NusA-HN and NusA-F proteins were expressed in soluble form in E. coli. The recombinant proteins were purified and used to immunise specific pathogen-free (SPF) chickens. ELISA results revealed that the insoluble and urea-solubilised inclusion bodies of the recombinant HN and F proteins, and the soluble NusA-HN and NusA-F proteins stimulated the production of antibodies that detect NDV. Among these antigens, the urea-solubilised HN IB appeared to induce the highest antibody titers. However, the chicken antibodies failed to neutralise the viral activities as shown in the tests such as haemagglutination inhibition (HI), neuraminidase inhibition (NI) and haemolysis inhibition (HLI). This explains the susceptibility of the immunised flocks to NDV infection upon the viral challenge. Despite of the presence of antibodies to NDV, none of the immunised chicken was protected against the viral challenge. Immunoblotting analysis on the interactions between the antigens and antibodies revealed that the anti-F antibodies did not bind to the denatured viral F glycoprotein, neither the anti-NDV serum detect the recombinant F protein. However, the anti-HN antibodies showed positive signals when used to probe the denatured viral HN glycoprotein, and in return,the anti-NDV serum detected the recombinant HN protein. This finding indicates the potential application of the E. coli produced HN protein as antigen for the detection of NDV antibody.